Introduction to health research methods : a practical guide - Jacobsen, Kathryn H. (Burlington, MA : Jones & Bartlett Learning, 2017)
"This clear, practical, and straightforward text demystifies the research process and empowers students and other new investigators to conduct their own original research projects. In five sections, Introduction to Health Research Methods describes the entire research process beginning with the identification of a research question and the selection of a study approach, proceeding through the collection and analysis of data and the preparation of a formal scientific report, and ending with academic and professional presentations and publishing. By breaking down the process into manageable steps, Introduction to Health Research Methods communicates the excitement and importance of health research and encourages readers to make their own contribution to improving the health of individuals and communities throughresearch."
1. Identifying a study question -- 2. Selecting a study approach -- 3. Designing the study and collecting data -- 4. Analyzing data -- 5. Reporting findings
Includes index
Keywords: Biomedical Research -- methods; Health -- Research -- Methodology; Medicine -- Research -- Methodology